Space Charge Dynamics in Epoxy Resins Under the Influence of a Long-Term High Electric Field at Various Temperatures - Zhang, Hongliang; Li, Kun; Jin, Hai; Li, Kangle; Li, Xiaonan; Liu, Peng; Peng, Zongren (Frontiers in Chemistry, 2022)
As the main insulating material of the ultra-high voltage (UHV) resin impregnated paper （RIP） bushing, the epoxy resin accumulates space charge under the DC voltage, which would affects the insulation properties of the bushing. In this paper, the evolutions of space charge accumulation and dissipation within the epoxy resin samples were measured under a long-term (24 hours) electric field of 60 kV/mm at 40℃, 60℃, 80℃ and 100℃, respectively. The experimental results show that the space charge transport in the epoxy sample was a long-time dynamic process. When the temperature was no more than 60 ° C, only the homo-charge accumulation was observed within the samples, which space charge distribution did not even reach stable after 24 h of applying voltage. When the temperature was no less than 80 ° C, the positive hetero-charge accumulation was observed at the interface between cathode/epoxy. Through analysis by fitting and numerical simulation, it was verified that the positive hetero-charge accumulation was caused by the limitation of holes extraction, and the transport of holes within the samples obeyed the jump conductance model.